Adapting a Family-Focused Diabetes Prevention Program for a Federally Qualified Health Center: A Qualitative Report. Issue 2 (April 2020) - Rivers, Patrick; Hingle, Melanie; Ruiz-Braun, Griselda; Blew, Robert; Mockbee, Joy; Marrero, David
Purpose: The purpose of the study was to explore the needs of high-risk Latinx/Hispanic women with a history of gestational diabetes who were patients at a Federally Qualified Health Center (FQHC) in anticipation of a future family-based program. Methods: Six focus group studies were conducted in partnership with El Rio Community Health Center, an FQHC in Tucson, Arizona. Thirty-nine women participated, each identified as Latinx/Hispanic, self-reported a history of gestational diabetes or prediabetes, and had at least 1 child aged 8 to 13. Three investigators independently reviewed transcripts from the focus groups to identify themes that reflected thematic saturation from participants' responses. Data coding and results were discussed as a group and any differences were collectively adjudicated. Results: All participants had a family member with diabetes and worried about their and their immediate family members' risk for developing the disease. The possible benefits of participating in a lifestyle prevention program were universally recognized, but multiple barriers to participation were described, including scheduling conflicts, access to childcare, transportation, and the need to involve additional family members to reinforce program objectives. Conclusions: There is a strong willingness to participate in a diabetes prevention program among respondents, but to be successful, interventions must be tailored to specific needs and challenges. Trying to apply existing prevention curricula with low-income Latinx/Hispanic populations may not be successful without adaptations.